Effect of the addition of alkaline earth sulfates to mullite ceramics on the corrosion and wetting by Al–Mg alloy. Issue 7 (July 2015) - Ibarra, M.N.; Almanza, J.M.; Cortés, D.A.; Escobedo, J.C.; Pech, M.; Martinez, R.
Abstract: Novel ceramics showing a high corrosion resistance were obtained by adding alkaline earth sulfates to mullite (Al6 Si2 O13 ). Powder samples of mullite, mullite–SrSO4 and mullite–BaSO4 were prepared. Disk pellets of 4 cm in diameter were conformed by uniaxial pressing at 78 MPa and sintered at 1450 °C for 6 h. Wetting experiments were carried out by the sessile drop test at 900 °C using an Al–7Mg alloy. After sintering, substrates of mullite, mullite–SrAl2 Si2 O8 or mullite–BaAl2 Si2 O8 were obtained. The contact angles between samples surface of alkaline earth sulfates containing mullite and molten alloy were higher than that corresponding to pure mullite, showing a non-wetting behavior. Cross-section analysis by SEM and EDS of samples after the wetting test showed that the corrosion products were spinel (MgAl2 O4 ) and periclase (MgO). The BaAl2 Si2 O8 -containing samples showed a higher corrosion resistance.